2019
DOI: 10.1107/s1600577519008853
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure nuclear inelastic scattering with backscattering monochromatization

Abstract: The capability to perform high‐pressure low‐temperature nuclear inelastic scattering on 125Te and 121Sb with a sapphire backscattering monochromator is presented. This technique was applied to measure nuclear inelastic scattering in TeO2 at pressures up to 10 GPa and temperatures down to 25 K. The evaluated partial Te densities of phonon states were compared with theoretical calculations and with Raman scattering measured under the same conditions. The high‐pressure cell developed in this work can also be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In addition, structural information can be obtained by hyperfine spectroscopies. Nuclear resonance scattering techniques have been developed to enable element-specific lattice dynamics characterization at ambient and high pressure and at low temperature. Here, we report the vibrational properties and lattice dynamics of α-Sb 2 O 3 , β-Sb 2 O 3 , and α-TeO 2 obtained by means of synchrotron radiation-based nuclear resonance scattering and INS. The experimental results are compared with DFT calculations and utilized to obtain the contribution of vibrational entropy to the α-Sb 2 O 3 to β-Sb 2 O 3 phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, structural information can be obtained by hyperfine spectroscopies. Nuclear resonance scattering techniques have been developed to enable element-specific lattice dynamics characterization at ambient and high pressure and at low temperature. Here, we report the vibrational properties and lattice dynamics of α-Sb 2 O 3 , β-Sb 2 O 3 , and α-TeO 2 obtained by means of synchrotron radiation-based nuclear resonance scattering and INS. The experimental results are compared with DFT calculations and utilized to obtain the contribution of vibrational entropy to the α-Sb 2 O 3 to β-Sb 2 O 3 phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…High pressure and low temperature nuclear forward scattering (NFS) measurements were performed at beamline P-01, PETRA III, DESY, Hamburg. The compact DACs are made from CuBe alloy and were installed into cryomagnetic system allowing for measurements down to about 3 K 28 . In order to assure that we measure from the same region of the sample, the high pressure cells were aligned to the beam in a way that we always hit the same part of the sample.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To fill this gap we carried out high pressure investigations in BFTO combining structural (XRD and Raman) and magnetic (Mössbauer) probes. In particular Synchrotron based Mössbauer measurements (nuclear forward scattering, NFS) are ideal to probe the magnetism at high pressures [26][27][28][29] . It is observed that magnetic order develops in BFTO at low temperature (5 K) and high hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 151 Eu is one of the most active isotopes researched with NRVS and other synchrotronbased nuclear scattering techniques in recent years for a variety of applications ranging from simple complexes to high pressure systems. [43][44][45][46][47][48][49][50] For the two complexes used in this study, it is important to compare the information obtained via 57 Fe and 151 Eu NRVS to understand, for example, whether the "introduced" Eu(III) occupies the outer Fe(III) site or the inner Fe(II) site in the PBlike structure, and to observe any subtle differences in the complexes containing either Fe(II) or Fe(III). These issues are the central tasks of this publication.…”
Section: Papermentioning
confidence: 99%
“…151 Eu NRVS spectra (for 1, 2, and 9) were recorded using a published procedure at APS 03ID. [43][44][45][46]50 An HHLM produced 21.5 keV radiation with ∼1.0 eV energy resolution, and an HRM with a "nested" Si(4,4,0)-Si(15,11,3)•2-Si(4,4,0) structure subsequently produced 21.5 keV radiation with 1.0 meV energy resolution, perfect for measuring vibrations. 59 The beam flux was ∼0.7 × 10 9 photons per s. 59 During NRVS measurements, the samples were maintained at a cryogenic temperature using a LHe cryostat maintained at 10 K. The analyzed real sample temperature was about 80 K. The total intensities collected from both the direct nuclear fluorescence at hν 1 and the internally converted electron L shell fluorescence at hν 2 [as shown in Fig.…”
Section: Eu Nrvs Measurementsmentioning
confidence: 99%